2023
DOI: 10.1177/02692163231152525
|View full text |Cite
|
Sign up to set email alerts
|

Communication in the context of glioblastoma treatment: A qualitative study of what matters most to patients, caregivers and health care professionals

Abstract: Background: Patients with glioblastoma have a poor prognosis and treatment is palliative in nature from diagnosis. It is therefore critical that the benefits and burdens of treatments are clearly discussed with patients and caregivers. Aim: To explore experiences and preferences around glioblastoma treatment communication in patients, family caregivers and healthcare professionals. Design: Qualitative design. A thematic analysis of semi-structured interviews. Setting/participants: A total of 15 adult patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Patients face decisions in a stressful situation where they are emotionally overwhelmed, and their abilities to receive information and be involved in decisionmaking are affected by strong emotions, a feeling of urgency and fear of decisional regret. [37][38][39][40][41][42][43] These feelings can influence patients' wish for and ability to participate in shared decision-making, as Lape et al 40…”
Section: Findings From Thematic Metasynthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Patients face decisions in a stressful situation where they are emotionally overwhelmed, and their abilities to receive information and be involved in decisionmaking are affected by strong emotions, a feeling of urgency and fear of decisional regret. [37][38][39][40][41][42][43] These feelings can influence patients' wish for and ability to participate in shared decision-making, as Lape et al 40…”
Section: Findings From Thematic Metasynthesismentioning
confidence: 99%
“…37,39,43,44,47,48,53,54 Physicians' perceptions of patients' wishes for treatment might also make it difficult to suggest no treatment, and physicians could provide treatment plans without addressing existing uncertainty and treatment limitations, sometimes motivated by a wish to meet the patients' expectations for treatment and to preserve hope. 37,41,43,47,55 In line with the limited perception of choices, some studies showed limited discussions of pros and cons of different options. 37,40,41,44,55,56 Medical specialists provided information on the suggested option, and at the same time tried to adapt the information to patients' individual needs.…”
Section: This Diagnostic Context [Patients With Spinal Metastatic Dis...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the Februari edition of Palliative Medicine two studies are published about patients with a glioblastoma. 2 Boele et al interviewed patients with a glioblastoma, caregivers, and healthcare professionals about their experiences and preferences around glioblastoma treatment communication. They conclude that effective communication, building trusting relationships, maintaining a sense of control, and being well-informed are identified as critical by patients, caregivers, and healthcare professionals.…”
mentioning
confidence: 99%